Ab initio study of the phonon and thermodynamic properties of the scheelite MWO4 (M = Ba, Sr or Ca) compounds. (July 2021) - Carvalho, I.P.; Lima, A.F.; Lalic, M.V.
Abstract: In this work, we performed the calculations based on density functional theory with different exchange and correlation energy approximations and employed the method of the constant force within the harmonic approximation, to study the phonon and thermodynamic properties of the three MWO4 (M = Ca, Sr or Ba) compounds with scheelite-type structure. In the first part of the work, we carried out an analysis of the performance of the local density approximation (LDA) and generalized gradient approximation of the Perdew-Burke-Ernzerhof revised for solids (GGA-PBEsol) on the computed phonon density of states, specific heat at constant volume, entropy and Gibbs free energy of the scheelite BaWO4 compound. Comparisons between calculated and experimental data showed that the GGA-PBEsol approach exhibited better performance. In the second part of the work, we extended the study of the thermodynamic properties to the SrWO4 and CaWO4 compounds, which are not presented in the literature, using the GGA-PBEsol approximation. It was found that the magnitude of the specific heat at the constant volume at high temperature respects the following order: BaWO4  > CaWO4  > SrWO4 . Moreover, it was verified a relation between M 2+ ionic radius in the scheelite MWO4 (M = Ba, Sr or Ca) and their entropy, Gibbs energy, and Helmholtz free energy. Highlights: Phonons and thermodynamics of the MWO4 (M = Ca, Sr, Ba) scheelites were studied. The study is performed by DFT in the frame of direct force constant method. GGA-PBE exchange-correlation functional reproduces experiment better than LDA. Thermodynamic functions of the SrWO4 and CaWO4 are calculated for the first time. Correlation between M 2+ ionic radii and thermodynamic functions is discussed.